DESIGN OF UNDIRECT GUY WIRE TENSION METER BASED ON STRAIN GAUGE - Sasmito, Agus; Irawadi, Yudi (Majalah Ilmiah Pengkajian Industri, 2019)
The safety of the tower is depend the tension of guy wire, where it must have the same tensile stress at all positions. To meet this requirement, the load cell guy wire is designed based on strain gauge. Load cell guy wire  is designed portable and it can detect stress of the guy wire indirectly. The main component of load cell is a beam, two hooks and a cylinder to form a bending moment force in the beam, the value of the bending moment on the beam will be directly proportional to the increase or decrease in force drag on guy wire. Design process of load cell doone using mathematical analysis, and then the load cell is calibrated by standard load cell, based on the data result of calibration is known that the stress at the guy wire load cell is close and under the yield stress of the load cell material, it is proved that load guy wire cell?s design result is safe to use.